Comparison of trend in chronic kidney disease burden between China, Japan, the United Kingdom, and the United States - Wen, Haoyu; Yang, Donghui; Xie, Cong; Shi, Fang; Liu, Yan; Zhang, Jiaming; Yu, Chuanhua (Frontiers in Public Health, 2022)
Chronic kidney disease (CKD) caused heavy burden globally. This study aimed to investigate the patterns and temporal variations in the burden of CKD in China, Japan, the United Kingdom (U.K.) and the United States (U.S.) from 1990 to 2019, and decompose the difference in CKD disease burden between 1990 and 2019 into demographic factors. From 1990 to 2019, although the age-standardized rate (ASR) of incidence remained stable in the four countries, and the ASR of mortality and disability-adjusted life years (DALY) have declined in four countries (except for the increase in U.S.), but the number of CKD incidence, death, and DALY increased significantly. The average disease burden per case in U.S. has increased between 1990 and 2019, with an increasing proportion of death-related disease burden. For the CKD due to diabetes and hypertension, whose incidences accounted for less than 25% of the total CKD, while it accounts for more than 70% of the deaths (except in U.K. with 54.14% in female, and 51.75% in male). CKD due to diabetes and hypertension should be the focus of CKD prevention and control. Considering the high treatment costs of CKD and ESRD, it is urgent and necessary to transform CKD treatment into primary and secondary prevention.